Warped Product Pseudo-Slant Submanifolds of a Nearly Cosymplectic Manifold. (31st July 2012) - Uddin, Siraj; Wong, Bernardine R.; Mustafa, A. A.
Abstract : We study warped product pseudo-slant submanifolds of a nearly cosymplectic manifold. We obtain some characterization results on the existence or nonexistence of warped product pseudo-slant submanifolds of a nearly cosymplectic manifold in terms of the canonical structures P and F .